2023
DOI: 10.3389/fpubh.2023.1276859
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and prevention practices related to dog-mediated rabies in Ethiopia: a systematic review and meta-analysis of observational epidemiological studies from inception to 2023

Beshada Zerfu Woldegeorgis,
Amanuel Paulos Genebo,
Amanuel Yosef Gebrekidan
et al.

Abstract: BackgroundRabies is a horrific and neglected zoonotic disease that kills thousands of people worldwide each year and continues to pose threats to public health. Prevention and control of dog-transmitted rabies require mapping the level of understanding, perception, and existing practices to minimize its impacts on health. Therefore, we undertook this systematic review and meta-analysis to pool evidence from available data on knowledge, attitudes, and prevention practices regarding the disease from studies cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Our approach to modelling dog owners’ overall understanding of rabies as a latent variable was novel and robust. It offered an advancement over previous studies on rabies that modelled rabies knowledge or understanding using observed data [ 52 ]. This is because knowledge is always latent and can never be fully measured [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to modelling dog owners’ overall understanding of rabies as a latent variable was novel and robust. It offered an advancement over previous studies on rabies that modelled rabies knowledge or understanding using observed data [ 52 ]. This is because knowledge is always latent and can never be fully measured [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of observational epidemiological studies on dog-mediated rabies in Ethiopia by Woldegeorgis et al (2023) highlights the critical gaps in attitudes and prevention practices, despite some level of knowledge about the disease Their study underscores the need for country-wide, cross-sectoral collaboration to realize global elimination strategies for dog-mediated human rabies. The findings reflect a broader trend in African epidemiology, where community engagement and education play a pivotal role in disease prevention and control.…”
Section: Epidemiological Practices In African Public Health Studiesmentioning
confidence: 99%